Investment efficiency in new hotel buildings in Croatia - Slobodan Ivanovic; Miroslav Pretula; Eddy Rot (UTMS Journal of Economics, 2012)
Abandonment of mass tourism in the late 80-ies of 20th century and attitude of humane tourism oriented to the needs and requirements of individuals, it is characterized by changes in the design and architectural design of hotel facilities. Features and functionality of hotel facilities are affected by trends in tourism demand. Tourism gets new features, which hotel companies must adapt. Individualism, humanism and hedonism are the guidelines that accompany the tourist industry in the 21st century. They determine the new considerations shaping and arranging hotel facilities, and the need for transformation of the hotel buildings designed for mass tourism in facilities for contemporary tourist who is aware of his needs, desires and aspirations. These trends should be monitored and the hotel industry in Croatia. The last decade marked by investments in reconstruction and modernization of existing hotel facilities, but investment in new hotel facilities are still minor. The reason for this is the fact that the hotel industry is low profitable activity, but also in the unfinished privatization, lack of domestic financial capital and the lack of attractiveness of the Croatia to attract foreign capital which would allow meaningful construction of new and rehabilitation of existing hotel facilities in line with trends in the tourism market. This paper critically examines the state of the hotel industry in the Republic of Croatia and its competitiveness in Europe, and it presents the results of research on the effectiveness of building a fictional hotel in Croatia, with a comparative analysis with European hotels.
Keywords: L83; G31; 330; hospitality; investment; investment efficiency